2018
DOI: 10.1017/s0033291718000697
|View full text |Cite
|
Sign up to set email alerts
|

The etiology of social aggression: a nuclear twin family study

Abstract: Although the specific NTF parameter estimates varied across informants, social aggression generally emerged as largely additive genetic (A = 0.15-0.77) and sibling environmental (S = 0.42-0.72) in origin. Such findings not only highlight an important role for individual genetic risk in the etiology of social aggression, but also raise important questions regarding the role of the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Reduced gray matter in the prefrontal region is associated with aggressive behaviors regardless of diagnosis of psychological disorder, and this suggests that aggression is affected by biological factors since many genetic factors come into play in the gray matter of the frontal cortex [ 27 ]. A long-term twin follow-up study showed that genetic factors play a major role in social aggression [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced gray matter in the prefrontal region is associated with aggressive behaviors regardless of diagnosis of psychological disorder, and this suggests that aggression is affected by biological factors since many genetic factors come into play in the gray matter of the frontal cortex [ 27 ]. A long-term twin follow-up study showed that genetic factors play a major role in social aggression [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of environmental factors on aggression varies depending on gender, with females affected relatively less by the environment [ 29 ]. To investigate the differences in the mediating effect of father-child communication on the association between aggression and the risk of IGD, a multi group structural equation model stratified by gender was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Social aggression is especially interesting in this regard, as it varies only minimally across sex (but may be slightly more common in girls; Card, Stucky, Sawalani, & Little, 2008). Ongoing work in the MSUTR sample has also found no evidence of sex differences in the etiology of social aggression, for either maternal or teacher informants (Slawinski, Klump, & Burt, 2018). Although these findings require replication, they suggest that the current findings for teacher informant-reports do not extend to all antisocial phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…However the influence of genes can be augmented by the environment such that it decreases with decreasing positive social feedback [ 37 ] or increasing parental negativity [ 38 ]. From the genetic influences, mainly additive genetic factors have been found to explain the variability; they accounted for 15-77% of the variance in social aggression [ 39 ] and up to 90% of the individual differences in baseline impulsive aggression in the longitudinal Quebec Newborn Twin Study [ 40 ]. Interestingly, the effects of genetic factors on aggressive behaviors can change over time [ 41 ] and the influence of genes on the variation of aggressive behaviors can change over development (18% genetic influence in early-middle adolescent to 47% genetic influence in middle adolescent) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Correlation between opposite sex DZ pairs for preferences for relationally aggressive media was negative and significantly less than for same sex DZ pairs (z = 2.47, p = 0.007) For CBCL aggression, the MZ correlations were significantly greater than the DZ correlations (z = 2.14, p = 0.016), with a heritability estimate of 0.60. Slawinski [ 39 ] The etiology of social aggression: a nuclear twin family study. Twin Study of Behavioral and Emotional Development in Children (TBED-C) 81.7% non-Hispanic White, 9.5% African American, 1.1% Native American, 0.8% Asian, 0.7% Hispanic 0.3% Pacific Islander and 5.9% multiracial or other.…”
Section: Methodsmentioning
confidence: 99%